Hubungan Aktivitas Leisure terhadap Kesejahteraan Psikologis pada Mahasiswa Tingkat I Program Sarjana Terapan Jurusan Okupasi Terapi Poltekkes Surakarta - Reny Ayu Damayanti; Haryanti Haryanti; Khomarun Khomarun (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: First-year university students are vulnerable to a decline in psychological well-being due to the adaptation process to the higher education environment and high academic demands. Leisure activities are seen as a strategy that can help maintain students' psychological well-being. Objectives: This study aims to analyze the relationship between leisure activities and psychological well-being in first-year students of the Applied Bachelor Program, Department of Occupational Therapy, Surakarta Health Polytechnic. Methods: The study used a quantitative design with a cross-sectional approach. A sample of 130 students was selected using a total sampling technique. Data collection used the Leisure Activity Scale (LAS) and Ryff's Scales of Psychological Well-Being (SPWB) questionnaires. Data analysis used the Spearman's rho correlation test. Results: The results showed a significant positive relationship between leisure activities and psychological well-being (0.479; p < 0.001). The higher the students' leisure activities, the higher their level of psychological well-being. Conclusion: Leisure activities play an important role in supporting the psychological well-being of first-year university students. Keywords: Leisure Activities, Psychological Well-Being, Mental Health, Occupational Therapy.